Законодавчі засади боротьби з організованою злочинністю та корупцією - Предместніков, О. Г.; Predmestnikov, O. H.; Іванцов, В. О.; Ivantsov, V. O.; Присяжнюк, І. І.; Prysiazhniuk, I. I.; Іванцов Володимир (Європейські перспективи. - 2024. - № 2. - С. 80-86, 2024)
Проаналізовано правову базу боротьби зі злочинністю та корупцією. У статті надано визначення понять «організована злочинність» і «корупція», розглянуто найважливіші закони, які встановлюють принципи подолання цих явищ у суспільстві. Законодавча політика України щодо протидії корупції та злочинній діяльності покликана сприяти формуванню та реалізації мети, завдань і методів державної діяльності.

The article analyzes the legislative principles of combating crime and corruption. The absence and inadequacy of legal policy, the imperfection of the legal framework, inconsistency and gaps in legal behavior at all levels, which leads to a lack of general understanding of the goals, methods and results of the national policy of Ukraine in the fight against crime and corruption. The purpose of this article is to study the legal framework for combating crime and corruption. Democracy, openness, transparency and public understanding of government actions are important in the fight against organized crime and corruption. Definitions of the terms «organized crime» and «corruption» have been established. The most important laws (both national and international) that establish the fundamental principles of solving these issues are considered. State regulation of organized crime and corruption involves the creation of norms, standards, formal and informal rules, which the state, in the form of local and central authorities, establishes for subjects carrying out activities aimed at ensuring the legal rights and interests of citizens, as well as achieving goals and objectives state authorities. The legislative policy of Ukraine on combating corruption and criminal activity is intended to contribute to the formation and implementation of the goal, tasks and methods of state activity in the prevention of corruption and criminal activity, as well as the fight against corruption and criminal activity. The fight against organized crime is a complex and long-term process that requires focus on one aspect and constant analysis of the situation. However, with the help of a systemic approach that involves both public and civil institutions and organizations, a real possibility of success in the fight against organized crime and the development of a safe and just society can be realized. Scientific works planned for the future should be considered in the context of improving legislation in this area.

Проанализирована правовая база борьбы с преступностью и коррупцией. В статье даны определения понятий «организованная преступность» и «коррупция», рассмотрены важнейшие законы, устанавливающие принципы преодоления этих явлений в обществе. Законодательная политика Украины по противодействию коррупции и преступной деятельности призвана способствовать формированию и реализации целей, задач и методов государственной деятельности.
Keywords: організована злочинність; корупція; закон; законодавчі засади; боротьба з організованою злочинністю; боротьба з корупцією; organized crime; corruption; law; legislative principles; fight against organized crime; fight against corruption; организованная преступность; коррупция; законодательные основы; борьба с организованной преступностью; борьба с коррупцией